1986
DOI: 10.1002/cyto.990070612
|View full text |Cite
|
Sign up to set email alerts
|

Orientation measurements of microsphere doublets and metaphase chromosomes in flow

Abstract: Obtaining information about the shape of particles from slit‐scan profiles is facilitated if the particles are oriented. Elongated particles orient in the nozzle of flow cytometers, but orientation may be disrupted before the particles get to the point of measurement. We have used our slit‐scan flow cytometer to investigate the orientation of microsphere doublets in a liquid jet in air, in flow across a glass surface, and in a 200‐μm‐square capillary tube as a function of distance from the flow chamber nozzle.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

1989
1989
1995
1995

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…When the laser beam is positioned within this region, 80%-90% of the bead doublets are correctly oriented. This maximum percentage is consistent with that determined for other instruments (Lucas and Pinkel, 1986). Farther from the inlet, the orientation becomes random, giving a relatively constant fraction of correctly oriented doublets of about 50 % .…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…When the laser beam is positioned within this region, 80%-90% of the bead doublets are correctly oriented. This maximum percentage is consistent with that determined for other instruments (Lucas and Pinkel, 1986). Farther from the inlet, the orientation becomes random, giving a relatively constant fraction of correctly oriented doublets of about 50 % .…”
Section: Resultssupporting
confidence: 90%
“…In fact, the value of slit scanning data would be restricted if one did not know the scanning axis of the object. Lucas and Pinkel (1986) have shown that a region exists in the flow cell of a flow cytometer in which the fluid flow is extensional, and in this region of accelerating fluid, objects with an aspect ratio greater than unity tend to align their longitudinal axis with the direction of flow. As the flow becomes fully developed, objects have a tendency t o tumble and thus take on a random orientation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, particles with dips in their fluorescence profiles have elongated shapes inducing them to align in the direction of flow (17). This process facilitates the slit-scanning analysis of particles such as sperm (3,111, cell aggregates (21), and chromosomes (1,2,5,6,9,12,18,19).…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports of work in this area are quite limited perhaps as a consequence of the high cost and performance limitations of early DSP systems. Examples include the slit-scan flow cytometric analysis of chromosomes (3,15,(17)(18)(19)(20)28,29,32), microsphere doublets (19), and plankton (8,12). Calculations of the pulse waveform features have involved pulse width ( 16,20,24, 3 1 ), the area-based centromeric index (3,15,17,IS), the depth of the dip in a pulse waveform (19), the banding pattern contained within a pulse waveform ( 17,18), and the pulse integral and time of flight (8,12).…”
mentioning
confidence: 99%